Intensivist-to-patient ratios in ICUs: is there a number?. Issue 2 (April 2015) - Ward, Nicholas S.; Howell, Michael D.
Abstract : Purpose of review: Growth in critical care services has led to a dramatic increase in the need for ICU physicians. The supply of intensivists is not easily increased and there is pressure to solve this problem by increasing the number of patients per intensivist. There is a scarcity of published data addressing this issue, and until recently, there were no guidelines on appropriate ratios of intensivists to patients. Recent findings: In 2013, the Society of Critical Care Medicine formed a task force to address this issue and published written guidelines to aid hospitals in determining their intensivist staffing. This study reviews the published data which can aid these decisions and summarize the SCCM Taskforce's recommendations. Summary: The complex nature of critical care patients and ICUs make it difficult to provide one specific maximum intensivist-to-patient ratio, but common-sense rules can be applied. These recommendations are predicated on the principles that staffing can impact patient care as well as staff well-being and workforce stability. Also, that worsening patient outcomes, teaching, and workforce issues can be markers of inappropriate staffing. Finally, if the predicted daily workload of an intensivist exceeds the time of a work shift, then adjustments need to be made.